ANALISIS SEMIOTIKA PESAN DAN NILAI MORAL YANG TERKANDING DALAM FILM “SANG PENCERAH” KARYA HANUNG BRAMANTYO - Widyastuti Fadhila; Neneng Sulasmi (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
This research starts from the idea that film as an art form, naturally cannot be separated from moral values ​​with the aim of assessing a person's quality. The film Sang Pencerah tells the story of Kiai Haji Ahmad Dahlan's struggle in spreading the idea of ​​Islamic renewal in Indonesia, making it an interesting object to analyze. This research uses a semiotic analysis method, with a descriptive qualitative approach, so as to be able to understand social phenomena in depth. Primary data sources are original information in the form of films, while secondary data sources include literature that supports and is relevant to the research topic. The analysis in this research is related to the message and moral values ​​in the film Sang Pencerah. The results of the research show that the film Sang Pencerah effectively uses visual meanings such as updating the direction of the Qibla with a compass which represents rationality and correction, the use of a blackboard symbolizing modern education and liberation from ignorance, caring for street children and the poor as a form of mutual respect and love, and the accusation of infidel kiai which reinforces that truth and progress often come at the price of resistance. These findings highlight how the film Sang Pencerah not only narrates history, but also semiotically builds understanding and moral values ​​that are relevant for society.